Sosialisasi Model House Of Quality Produk Eceng Gondok Dalam Perbaikan Mutu Pada Umkm Rumah Anyamandiri di Kota Makassar - Nadzirah Ikasari Syamsul; S Bahri; Mulyadi -; Hanafi R; S Asmal; F Mardin; M Rusman; I Bakri; N Syamsul; D R Mudiastuti; S Mangenre; I Setiawan; S Parenreng; A B R Indah; M A Darmawan; K Amar (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2020)
In the midst of the current pandemic, of course, many businesses are feeling the impact of financial decline. However, MSME actors in each region or city this incident could be an opportunity to improve their welfare. Micro, Small and Medium Enterprises (MSMEs) have an important role in the economy of Indonesian society. Several aspects of the role of SMEs in the life of small communities, namely, facilities to alleviate the community from the abyss of poverty, means of leveling the economic level of the small people, and providing foreign exchange income. By encouraging MSMEs to upgrade to grades, it can reduce the poverty rate by around 20% or the equivalent of removing 5 million people from poverty. In addition, it can reduce the inequality rate by about 4%. Therefore, support from various parties to improve quality in the midst of the current pandemic is needed. One of the MSMEs that currently has superior products is water hyacinth sandals and woven bags, namely the Anayamandiri UMKM assisted by the provincial Dekranasda. Improvement and improvement of product quality are basic things that must be owned by MSME actors in order to maintain and increase the number of customers. Therefore, a Quality Function Development Method is an approach to customers by creating a Voice of customer and being able to design a house of quality matrix for each UMKM product